Perceived control decisions in preparation for a summative achievement test in higher education - van der Linden, Jeroen; van Schilt-Mol, Tamara; Nieuwenhuis, Loek; van der Vleuten, Cees (Frontiers in Education, 2023)
Most courses in higher education finish with one or more assessments which commonly all have to be passed. In these courses, student learning is commonly measured using conventional classroom tests, therefore test preparation is a common task for students. In higher education, compared with students’ prior education, they are faced with a more complex curriculum and have to perform their studies with less guidance and limited resources. Therefore, effective and efficient test preparation is important. A strategy to help students study effectively in the context of test preparation is to make the appropriate control decisions, for instance to cease test preparation on specific content and (re)study other subjects that need attention. These control decisions are an important psychological aspect of the test preparation study process. We conducted a qualitative study on how students made control decisions in a test preparation period for a knowledge test in Educational Sciences. The study was conducted with students of a teacher training programme at a University of Applied Sciences in the Netherlands. Results show that different progressions of learning judgments and the self-efficacy of students led to two different saturations. This in turn led to students making either no, inaccurate, or accurate control decisions. This article discusses the impact and practical implications of these insights.